Generative processes of social vulnerability to flood risk: A proposal for the strategic management of social impacts - Aznar-Crespo, Pablo; Aledo, Antonio; Ortiz, Guadalupe; Vallejos-Romero, Arturo (Current Sociology, 2024)
The mainstream approach of social vulnerability to flood risk faces some challenges regarding its ability to address the complexity of its causal processes. The objective of this study was to analyse the causal processes of social vulnerability to flood impacts from a relational perspective. To this end, a social network analysis was performed that identified the conditions and causes of social vulnerability and systematically articulated the relationships between them. This analysis was tested on the specific case of flood risk on the coast of the province of Alicante (SE Spain). To ascertain the conditions and causes of social vulnerability to flood risk, a multidisciplinary group of local experts was consulted, and the resulting data processed in a relational way using Atlas.ti and Gephi softwares. The result was a social vulnerability network comprising 84 nodes and 189 edges distributed into four dimensions: the adaptive capacity of tourists, socio-economic structure, land use planning and risk management. The information was ranked for betweenness centrality, revealing the components with highest causal power of social vulnerability to social impacts in flooding events: low flood risk awareness, economic growth based on real estate boom, property speculation and lack of political interest in flood risk management. This proposal places emphasis on the driving forces of social vulnerability and not exclusively on the specific adaptive conditions of the population, which allows a strategic identification and management of generative forces that ultimately induce the social impacts of floods.
Keywords: Flood Risk Management; Social Impacts; Social Vulnerability; Climate Change